Designing Dance Learning Videos using 2D Animation and Live Action Techniques for Elementary Schools - Angga Permana Putra; Riyan Abdul Aziz; Febrianta Surya Nugraha (Formosa Journal of Applied Sciences, 2023)
Learning dance is an important aspect in the elementary school (SD) curriculum to develop creativity and appreciation of art in children. However, conventional learning methods are often less interesting and less motivating for students. This research uses a qualitative-based design and development approach. The sample in this study was class 4 of SD N 3 Kwarasan. The next stage is the production process, where dance learning videos using 2D animation techniques and live action are made. 2D animation techniques are used to illustrate dance movements and steps in a visual and interesting way, while live action is used to show the execution of a dancer who teaches dance movements directly.